Reviews (New blackfriars, 1968)
THE COVENANT AND THE KINGDOM, by Joseph Rymer. PRAYER AND PROVIDENCE, by Peter Baelz. AUTHORITY IN A CHANGING CHURCH, by John Dalrymple and others. THE PARADOX OF GUILT: A CHRISTIAN STUDY OF THE RELIEF OF SELF-HATRED, by Malcolm France. A DICTIONARY OF CHRISTIAN ETHICS, edited by John Macquarrie. MORALS IN A FREE SOCIETY, by Michael Keeling. BORN TO HUNGER, by Arthur Hopcraft. OVERSEAS AID, Campaign Booklets for Overseas Aid, by Jonathan Power. THE HASLEMERE DECLARATION.